Burnout and Sources of Stress among Primary and Secondary Teachers in the Republic of North Macedonia - Gorica Popovska Nalevska; Marina Kuzmanovska; Sonja Rizoska Jovanovska (Journal of Research in Education and Pedagogy, 2025)
The study focuses on professional burnout and its sources of workplace stress among teachers. Burnout, as a complex psychological phenomenon, is characterized by emotional exhaustion, depersonalization and reduced professional efficiency. Teachers play a crucial role in the development of our future generations and their well-being is central to their ability to effectively fulfil this role. The general aim of the research is to measure burnout levels and sources of stress among primary and secondary teachers who are working in public schools in the Republic of North Macedonia, by examining the degree of emotional exhaustion, depersonalization and personal accomplishment. The research sample is randomly chosen and consists of 320 teachers. To collect data, a personal information form and Maslach Burnout Inventory were used to measure burnout levels of teachers. The obtained results found that primary and secondary teachers in public school in Republic of North Macedonia experienced a high level of emotional exhaustion and an average level of depersonalization and personal accomplishment dimension. Emotional exhaustion represents a critical warning sign of burnout, signaling the need for individual and organizational interventions to restore balance and resilience. The research detects nine significant factors that cause stress and professional burnout among teachers. The present study has contributed to the field by providing new insights into the stress and burnout experienced by primary and secondary teachers and should encourage education policies makers, national and local education authorities in developing a healthy, safe and productive environment for the growth and development of all involved in. Instead of looking at teacher burnout as an individual problem, leaders in education must shift their focus to assess the problem as a systemic, institutional, or policy-based issue.